Pengaruh Kepemimpinan dan Motivasi Kerja terhadap Kinerja Pegawai Balai Besar Meteorologi, Klimatologi, dan Geofisika Wilayah II - Tangerang Selatan - Ramadhani, Sandrina Windi (Prodi Manajemen, Fakultas Ekonomi, Universitas Pamulang, 2024)
This study aims to determine the influence of leadership and motivation on the performance of employees of the Center for Meteorology, Climatology, and Geophysics Region II South Tangerang. The research methods used in this study are associative methods and data collection with questionnaire techniques, interviews and observations. This study used a saturated sample with 76 respondents. Data analysis method with validity test, reliability test, normality test, multiple linear regression equation, correlation coefficient, determination coefficient, and significance test. The results of comprehensive leadership research affect employee performance because the significant value is below 0.05. Work motivation partially affects employee performance because the significant value is below 0.05. Simultaneously, Leadership and Work Motivation have a positive and significant effect on Employee Performance significantly with an F value 51.649 > F> table 3.18 with a coefficient of determination value of 56.8%.